2019
DOI: 10.1371/journal.pone.0221968
|View full text |Cite|
|
Sign up to set email alerts
|

Lower prevalence of Blastocystis sp. infections in HIV positive compared to HIV negative adults in Ghana

Abstract: Background Sub-Saharan Africa is endemic for intestinal parasites and distinguished for the largest burden of HIV cases. Blastocystis sp. is one of the most common protists infecting humans but its role in human disease is still controversial. Aim of this study was to investigate the prevalence of Blastocystis sp. in HIV positive and negative adults in Ghana and its association with immune status and other risk factors. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
(54 reference statements)
1
11
0
2
Order By: Relevance
“…Over the last decade, Blastocystis has been studied widely, but it remains unclear whether it is pathogenic [ 8 ]. Some studies report an association between Blastocystis and gastrointestinal symptoms, such as abdominal pain, diarrhea, vomiting, constipation, and irritable bowel syndrome (IBS) [ 5 , 9 , 10 ], whereas other investigations failed to prove any correlation between Blastocystis and health issues [ 11 , 12 ] or suggest that Blastocystis could be considered normal or beneficial for the microbiota [ 13 , 14 ]. Blastocystis transmission is generally associated with poor access to healthcare and unsanitary living conditions around the world [ 3 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, Blastocystis has been studied widely, but it remains unclear whether it is pathogenic [ 8 ]. Some studies report an association between Blastocystis and gastrointestinal symptoms, such as abdominal pain, diarrhea, vomiting, constipation, and irritable bowel syndrome (IBS) [ 5 , 9 , 10 ], whereas other investigations failed to prove any correlation between Blastocystis and health issues [ 11 , 12 ] or suggest that Blastocystis could be considered normal or beneficial for the microbiota [ 13 , 14 ]. Blastocystis transmission is generally associated with poor access to healthcare and unsanitary living conditions around the world [ 3 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted June 20, 2020. ; https://doi.org/10.1101/2020.06.17.20134064 doi: medRxiv preprint to showed associating Blastocystis with a healthy microbiome (8,9), a rich diet in vegetables (53) and a better immune status (7). Some studies found a positive correlation between Blastocystis and bacterial richness which suggests that Blastocystis is most common in people with healthy bacterial flora and negative correlated to Bacteroides that is observed more prevalent in unhealthy people being able to use Blastocystis as to determine the health of the individual rather than the bacterial composition (8,9,54).…”
Section: Regardless Of These Distribution the Outcome Do Not Show A mentioning
confidence: 99%
“…Blastocystis is a protozoa found in the gut of humans and animals (1,2), but it remains unclear whether it is pathogenic (3). Some researchers report an association between Blastocystis and gastrointestinal symptoms and diseases (4,5) whereas other investigations fail to prove any correlation between both (6,7) or suggest Blastocystis could be consider as normal or beneficial for the microbiota (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…За даними різних досліджень, Blastocystis spр. виявляють у 10-15 % людей у розвинених країнах та 50-100 % -в країнах, що розвиваються [6,7] ................................................................................ [31]. За результатами нашого дослідження, при обстеженні 250 ВІЛ-позитивних пацієнтів і 170 клінічно здорових дорослих частота виявлення Blastocystis spр.…”
Section: клініко-unclassified